Rainbow trout slow myoblast cell culture as a model to study slow skeletal muscle, and the characterization of mir-133 and mir-499 families as a case study - da Silva Duran, Bruno Oliveira [UNESP]; Dal-Pai-Silva, Maeli [UNESP]; de la Serrana, Daniel Garcia (The Company of Biologists, 2020)
Muscle fibres are classified as fast, intermediate and slow. In vitro myoblast cell culture model from fast muscle is a very useful tool to study muscle growth and development; however, similar models for slow muscle do not exist. Owing to the compartmentalization of fish muscle fibres, we have developed a slow myoblast cell culture for rainbow trout (Oncorhynchus mykiss). Slow and fast muscle-derived myoblasts have similar morphology, but with differential expression of slow muscle markers such as slow myhc, sox6 and pgc-1α. We also characterized the mir-133 and mir-499 microRNA families in trout slow and fast myoblasts as a case study during myogenesis and in response to electrostimulation. Three mir-133 (a-1a, a-1b and a-2) and four mir-499 (aa, ab, ba and bb) paralogues were identified for rainbow trout and named base on their phylogenetic relationship to zebrafish and Atlantic salmon orthologues. Omy-mir-499ab and omymir-499bb had 0.6 and 0.5-fold higher expression in slow myoblasts compared with fast myoblasts, whereas mir-133 duplicates had similar levels in both phenotypes and little variation during development. Slow myoblasts also showed increased expression for omy-mir-499b paralogues in response to chronic electrostimulation (7-fold increase for omy-mir-499ba and 2.5-fold increase for omy-mir-499bb). The higher expression of mir-499 paralogues in slow myoblasts suggests a role in phenotype determination, while the lack of significant differences of mir-133 copies during culture development might indicate a different role in fish compared with mammals. We have also found signs of sub-functionalization of mir-499 paralogues after electrostimulation, with omy-mir-499b copies more responsive to electrical signals.
Keywords: Cell culture; Electrostimulation; MiRNA; Myoblasts; Slow skeletal muscle